1978
DOI: 10.1111/j.1399-6576.1978.tb01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Local Adrenaline Infiltration During Halothane Anaesthesia and Adrenergic Beta‐Receptor Blockade in Man

Abstract: Adrenergic beta-receptor blocking agents, alprenolol, propranolol and practolol were given as a prophylactic measure to patients undergoing middle-ear microsurgery where adrenaline was deliberately infiltrated during halothane-N2O/O2 anaesthesia. These three beta blockers did not differ in their action on heart rate, arterial blood pressure, right ventricular pressure, CVP or peripheral pulse wave in equipotent doses, which were 0.04 mg/kg for alprenolol and propranolol and 0.4 mg/kg for practolol in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Lidocaine (xylocaine) is the main anesthetic used in our operations. It is characterized by a rapid onset and intermediate duration of action [15,16]. No adverse effects were found in our series.…”
Section: Discussionmentioning
confidence: 48%
“…Lidocaine (xylocaine) is the main anesthetic used in our operations. It is characterized by a rapid onset and intermediate duration of action [15,16]. No adverse effects were found in our series.…”
Section: Discussionmentioning
confidence: 48%
“…It has been reported that, sensation of noise and anxiety were the most common discomforts but the majority of patients preferred local anesthesia 8,9 .In our questionnaire survey, patients scored their discomfort of pain, body and neck movement, anxiety and noisy sensation from grade 0 (no discomfort) to 4 (extreme discomfort), corresponding to a value lower than "1" indicating "mild." Most patients 6055 (85.89%) experienced pain only at the beginning of the surgery because of numerous injections of the local anesthetic.…”
Section: Discussionmentioning
confidence: 98%